Exploring the Protective Effects of Abrus precatorius in HepG2 and N-Nitrosodiethylamine-Induced Hepatocellular Carcinoma in Swiss Albino Rats: Protective effect of Abrus procatorius against hepatoarcinoma - Ramaswami Kartik; Chandana Venkateshwara Rao; Palpu Pushpangadan; Sunil Prakesh Trivedi; Gaddam Dayanand Reddy (Iranian Journal of Pharmaceutical Sciences, 2010)
This study was designed to explore the protective effects of Abrus precatorius L. (Leguminosae) (AP) in HepG2 cells and N-nitrosodiethylamine (NDEA) induced hepatocellular carcinoma in Swiss albino rats. The effects of aqueous/ethanolic (50%) extract of AP on hepatic markers, haematological and histopathological parameters, and antioxidant enzymes were evaluated in NDEA (200 mg/kg and CCl4, 3 ml/kg body weight) induced experimental hepatocarcinogenesis in Swiss albino rats. In addition, cytotoxicity of the extract and its effect on the expression on p53 were studied in human hepatoma cell line (HepG2). Results obtained from cytotoxicity studies showed that the AP extract has strong cytotoxic effects on HepG2 cells. The expression of p53 was markedly increased and maintained at high level from 6-12 hr with 100 μg/ml of AP extract. A decrease in the mean and relative liver weights in AP extract treated group at a dose of 100 and 200 mg/kg was observed compared to the control group. It was also demonstrated that AP extract provided significant protection against hepatic lipid peroxidation and increased antioxidant enzymes’ activities such as superoxide dismutase, catalase, glutathione peroxidase, glutathione S-transferase and reduced glutathione levels. In a dose-dependent manner, the AP extract reduced the NDEA-induced elevated levels of various hepatic markers such as serum glutamate pyruvate transaminase, serum glutamate oxaloacetate transaminase, alkaline phosphatase, total bilirubin and gamma glutamate transpeptidase. The haematological paremater viz. RBC, WBC and haemaglobin was restored upon treatment with AP extract at 100 and 200 mg/kg. Histopathology of the liver was also carried out to mark the pathological changes in groups under study. The results of these studies demonstrate the protective effect of AP extract against NDEA induced hepatocarcinogenesis in Swiss albino rats and in HepG2 cell.